Literary Agon in the Light of the Knight’s Cultural Model - Skibska, Anna Maria (Poznańskie Studia Slawistyczne, 2019)
This essay – actually a scientific article included in the frame composition – is devoted to the innovative interpretation of literary agon in terms of the knight ethos on the background of Harold Bloom’s “anxiety of influence”, additionally enriched with references to Aeschylus’ and Eurypide’s “duel” in the Frogs by Aristophanes. On theoretical and methodological ground, the main research path is associated with an additional interpretation of Harold Bloom’s idea of intervals.